Public Access to Environmental Information: A Legal Right or Media Privilege? - Syed Mohammad Tahir Gohar; Dr. Abida Abdul Khaliq; Amna Fazail (Social Science Review Archives, 2025)
The availability of environmental information has turned out to be one of the pillars of modern environmental management, which guarantees transparency, accountability and citizen involvement in the decision-making process. Although the global law, especially the principle 10 of Rio Declaration 1992 and the Aarhus Convention, recognizes the right to access to environmental information by the people, the application of the principle in developing countries is still patchy. In Pakistan, although there is constitutional protection of freedom of information and the rights of a healthy environment were judicialized, freedom to access environmental information is still generally viewed as a privilege that is enjoyed by the media and civil society actors, but not as a right that should be enforced by everyone in general. This essay looks at the legal framework of environmental information in Pakistan and whether it is a legal right that should be available to every citizen in the country or a viable privilege to the media organizations and environmental activists. The analysis of the statutory tools of the Right of Access to Information Act 2017 and the Pakistan Environmental Protection Act 1997 and judicial interpretations of the higher courts have been used in the study to draw the progress and gaps in the system in the operationalization of transparency in environmental governance. The paper then concludes by giving policy and legal proposals to democratize environmental information that can close a gap between the law and the empowerment of the people in the matters of the environment.